Prenatal Diagnosis of Vesicorectal Fistula. Issue 1 (March 2017) - Correia, Patricia; Moreira, Marta; Rodrigues, Maria; Inocêncio, Gonçalo
Abstract : Abstract: Anorectal malformations are a rare condition difficult to diagnose in the prenatal period. It can be suspected if distal bowel appears dilated in the first-trimester ultrasound or if intraluminal echogenic foci are detected during the second-trimester scan. We report a case with these ultrasound signs (dilated sigmoid at the first trimester and intraluminal echogenic calcifications at the second trimester), in which a vesicorectal fistula image was obtained. This is the first published prenatal image of a vesicorectal fistula.